Effectiveness of the Al-Kort program in developing decision-making skills for high school principals in Riyadh city - Asiri, Naima Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2017)
The aim of this study is to investigate the impact of the integration of Al-Kort program in the development of decision-making and decision-making skills among high school principals in Riyadh city. The experimental approach was applied by the two experimental groups of secondary school principals in Riyadh, which are taught using Kurt's program, and the effectiveness of this study is based on the dependent variables of the achievement and decision making skills and the control group. On the variables related to educational achievement and decision-making skills of school principals. The content of two groups of high school principals in Riyadh has been enriched with skills-oriented activities in three areas of thinking derived from the CO program RT is: expanding the field of perception, organization, and problem solving.The results of the study showed a positive effect on the role of Al-Kort program (for high school principals in Riyadh) in the development of decision-making skills. The experimental group of the training program for the development of decision-making skills showed a positive difference of statistical significance in the experimental group (65%), The impact of the Quart program (for secondary principals in Riyadh) is reflected in raising the level of decision-making skills of students, expanding their perceptions, organizing their information, solving their problems, and making appropriate decisions. The study recommended the integration of the courteous program in the development of decision-making skills for secondary school principals to enhance the decision-making capacity, in addition to the need to hold courses, seminars and workshops for managers to introduce thinking skills and programs for their development and to provide a school environment that encourages them.The implementation of the Al-Kort program has led to the development of skills, the ability to make decisions and improve the level of academic attainment among high school principals in Riyadh.The impact of out-of-school training has had a clear impact, making training programs part of the daily trainees' practices in the various areas of human activity that require it.
Keywords: cognition; organization; problem solving; tribal knowledge; academic achievement